Cobalt-catalyzed intermolecular stereoselective bisbenzylation of alkynes. Issue 13 (25th March 2015) - Komeyama, Kimihiro; Asakura, Ryota; Fukuoka, Hiroshi; Takaki, Ken
Graphical abstract: Abstract: CoBr2 /P(OMe)Ph2 is found to be an effective catalyst-system for intermolecular bisbenzylation of alkynes with various benzyl bromides in the presence of manganese reductant. The transformation can be carried out under mild conditions, giving rise to stereocontrolled cis -1, 2-bisbenzylated alkenes in good yields.